Radiation effect on three dimensional vertical channel flow through porous medium - Guria, M. (Zielona Góra: Uniwersytet Zielonogórski)
The flow of a viscous incompressible fluid through a vertical channel in the presence of radiation immersed in a porous medium has been studied. Approximate solutions have been obtained for the velocity and temperature fields, shear stresses and rate of heat transfer using the perturbation technique. It is found that the primary velocity decreases with an increase in the radiation parameter as well as the Prandtl number for cooling of the plate.
Keywords: three-dimensional; injection; periodic suction; permeability; porous medium